Stimuli‐Free and Biocompatible Hydrogel via Hydrazone Chemistry: Synthesis, Characterization, and Bioassessment. (21st November 2018) - Nada, Ahmed A.; Soliman, Ahmed A. F.; Aly, Amal A.; Abou‐Okeil, Ashraf
Abstract : Functionalization of starch with oxidative cleavage reaction to yield the corresponding dialdehyde derivatives has been employed as an approach for gel formation via Schiff's base reaction. However, this reaction is known as reversible and hydrolysable in aqueous solutions. In this study, the potential of hydrazone chemistry to be used in the synthesis of stimuli‐free and stable hydrogels is investigated. Soluble starch is selectively oxidized to give aldehydic‐starch with different aldehyde contents 39.9, 34.6, and 22.6 aldehyde group/100 anhydroglucose unit (AGU). Adipic dihydrazide was used as an α‐effect nucleophile to react with the dialdehyde starch and obtain stable hydrazone‐based and stimuli‐free hydrogels. Hydrazone chemistry of aldehydic‐starch and adipic dihydrazide (AD) is demonstrated by spectral analysis. As well, the biocompatibility with human skin fibroblasts cells is investigated using a cytotoxicity assay. SEM images show the pore sizes vary from 575 to 4752 nm related to AD concentrations. The swelling degree recorded an increase of 900%, 500%, and 600% at pH 4, pH 7, and pH 9, respectively. Hydrogels showed varied mechanical behavior as a function of AD concentrations. Abstract : The capacity of hydrazone chemistry to be used in the synthesis of stimuli‐free and stable hydrogels is investigated via a selective oxidation of soluble starch to give aldehydic starch. Adipic dihydrazide is used to react with the dialdehyde starch in order to obtain stable hydrazine‐based and stimuli‐free hydrogels. The hydrogels show varied mechanical and swelling behavior with respect to their biocompatibility.